ZINE DESIGN AS A POTENTIAL INFORMATION MEDIA NAGREG KENDAN TOUR TO YOUNG ADULTS IN JAVA WEST - Adiyasa, Vanessa; Denny Nugraha, Novian; Soedewi, Sri (Telkom University, 2024)
Nagreg Kendan Village or commonly known as Kendan Village is a villagelocated in Nagreg District. Nagreg Kendan Village has plans to create a tourist village with various potentials in it, starting from the potential of the Sanghyang Anjung site which isfamous for its myths by local residents and tourists to a workshop for making bricks made from the sand of the Kendan hill itself. It is hoped that the creation of a tourist village canintroduce other potentials of Nagreg Kendan village to the wider community, especially to young adults who are interested in visiting a tourist village. To achieve this goal, theresearch method used is by conducting observations in Nagreg Kendan Village, interviews with local residents, and using literature studies related to the media that will be used. Themedia that will be used as a medium of information regarding tourism potential in Nagreg Kendan Village is art photography so that young adults are more interested in getting to know Nagreg Kendan Village better. Keywords: zine, travel journals, tourism villages, information media, art photography